Processing of Kapok Fiber into Biodegradable Pellets for Efficient Oil Absorption - Kobal, Vinod Kanna (Universiti Teknologi PETRONAS, 2016)
As industrializations are being expanded rapidly, environmental concerns are highlighted often through various media, especially water pollution. There many causes for water pollution but the significant cause is oil spill. Source of oil spill varies depends on the situation. In this project, source of oil spill been narrowed down to road tanker accident while transporting crude oil, crude palm oil and lubricants that possesses threat to the fresh water supply. The constraints in the current oil spill cleanup method have led to the recent interest in developing alternative cleanup method. Besides that, raw kapok as oil sorbent are difficult to apply, store and handle. In this particular project, the interests focus on Kapok fiber due to its hydrophobic and oleophilic characteristics. The main goal of this project are to characterize the physiochemical properties of raw kapok and formation of pellet, to investigate and compare the water sorption capacity, oil retention capacity and oil sorption capacity of raw kapok and pelletized kapok and to investigate the selectivity of raw kapok and kapok pellet for oil and water mixture.